ANALISIS FAKTOR LINGKUNGAN BELAJAR YANG MEMPENGARUHI HASIL BELAJAR SISWA - Ayu Yarmayani; Diliza Afrila (Universitas Batanghari Jambi, 2018)
Abstract: This research was aimed to find out (1) Description of X class learning environment at SMA Negeri 8 Jambi City, and (2) Factors of learning environment which affect students learning outcomes of X Class at SMA Negeri 8 Jambi City. The type of this research was quantitative descriptive research. The population in this research was 602 students. Technique used to take sample in this research was random sampling, selected 100 students as sample of the research. Technique to collect data in this research was spreading the questionnaire to the research respondents and interviews. Technique to analyze data in this research was factor analysis by using program of SPSS Version 16. The result of research indicated that (1) learning environment variables were in enough category with average 3,91 and Response Achievement Level (TCR) equal to 78,26, and 2) There were 10 (ten) dominant factors which affected students learning environment, namely (a) Factor 1 which was given teaching method, which consisted of statement items F6.1, F6.2, F6.3, F7.2, and F7. 4, (b) Factor 2 which was given the identity of the relation between the family members, which consisted of the statement items F2.2, F2.3, and F14.3, (c) Factor 3 which was given the identity of the community life form, F9.3, F10.1, F14.1 and F14.2, (d) Factor 4 identified the learning instrument, which consisted of the statement items F9.2, F10.2, F10.3, and F12.2, (e) Factor 5 which was given the identity of the parent's understanding, which consisted of the statement items F3.1, F5.1, F5.2, and F8.4, (f) Factor 6 which was given the identity of the home atmosphere, which consisted of statement items F1.3 and F3.2 (g) Factor 7 which identified teacher relation with student, consisted of statement items F7.1, F7.3, and F12.1, (h) Factor 8 identified the school discipline, consisted of statement items F9.1, and F9.3, (i) Factor 9 identified the friends’ interactions consisted of statement items F8.2 and F13.2, and (j) Factors 10 which was given the identity of the parents’ economic status, which consisted of statement items F3.3 and F4.1.Keyword: Factor Analysis, Learning Environment, Learning Outcomes